Meaning in Life in Long-Term Recovery in First-Episode Psychosis: An Interpretative Phenomenological Analysis - O'Keeffe, Donal; Keogh, Brian; Higgins, Agnes (Frontiers in Psychiatry, 2021)
Background: Meaning in Life (MIL) is a central aspect of service user defined personal recovery in mental health. It is unclear whether current knowledge regarding MIL is applicable to the lives of those who have experienced psychosis. As it was not possible to locate any study examining service user perspectives on MIL in first-episode psychosis (FEP), conducting in-depth qualitative research in this area offers an opportunity to develop a conceptualisation of MIL that may be transferable to the broad psychosis spectrum. Aim: The aim of the study was to explore how people find, develop, and maintain MIL approximately 21 years after their FEP diagnosis. Materials and Methods: The study aim was addressed using Interpretative Phenomenological Analysis (IPA). Participants were members of an epidemiologically complete FEP incidence cohort in Ireland. Purposive maximum variation sampling enabled the recruitment of a sample balanced across remission status, age at time of FEP onset, and gender. Semi-structured interviews were conducted circa 21 years post FEP with 16 participants. Data analysis was guided by IPA procedures. Results: Participants experienced MIL as awareness of connectedness to context – the interrelated conditions they existed in (their relationships with the self, others, systems, the environment, and time). Awareness of connectedness to context occurred in five main ways: Being myself – de-othering and authenticity (Enacting identity); Becoming significant where the self is witnessed (Belonging in life); Generating meaning within and beyond systems (Independence); Shaping and being shaped by life (Agency and patiency); and Integrating different perspectives of time (Reconciling temporality). Conclusions: Findings offer the first in-depth understanding of how people diagnosed with a FEP experience MIL in mid-later life recovery. Current tripartite MIL theories do not fully represent the array of MIL perspectives articulated by our participants. MIL concepts developed are potential areas for intervention for mental health services seeking to implement the recovery approach. Findings can be used to foster optimism among service users and their supporters for MIL attainment in psychosis and offer guidance for education, clinical practice, policy, and future research.